Is the United Arab Emirates Capable to Create a Green and Sustainable Future? - Almheiri, Abdulla Khalifa (2015)
A plethora of research has established that the anthropogenic activity triggered climate changes can elicit catastrophic consequences, jeopardizing the existence of life on earth. For assuaging such a looming peril, international organisations have recommended taking suitable steps so much so that the global mean temperature do not increase beyond 2◦ C. This can be achieved by intensive endeavours for attenuation of the carbon footprint by undertaking greener and sustainable approaches in diverse sectors of life including energy, water management, lifestyle etc. According to published reports UAE has virtually the highest carbon footprint in the world partially owing to its rapid development over the last few decades. Motivated by the inspirational and enthusiastic leaders, UAE is determined to take necessary measures to go green and sustainable in virtually each and every sector of life and living. The current research intends to evaluate various criteria to elucidate weather UAE is at all capable of a green and sustainable future. Such an assessment involves a detailed evaluation of a number of aspects including, motivation from the leadership, levels of awareness and motivation of the nationals, evaluation of the current achievements and future prospects. We also performed simulation studies for better explication. Overall our studies indicate that, notwithstanding that a plethora of works needs to be done on this arena; UAE definitely looks to be capable of a green and sustainable future.